Ichthyofanal Diversity from Ambadi Dam, Taluka Kannad, District – Aurangabad (M.S.) - Sonawane S.R2, Ubarhande S.B1* , Jagtap J.T2 and (Recent Research in Science and Technology, 2011)
Ambadi dam is perennial water resource for human consumption and also helpful for the agriculture and fisheries in taluka Kannad, district Aurangabad. Keeping a view that Ichthyofaunal diversity of Ambadi dam is correlated to aquatic ecosystem, present investigationÃ‚Â was carried out during the study period from May 2006 to April 2008, and it was observed that the ichthyofauna belongs to 08 orders 11 families 22 genus and 27 species while Cyprinidae family is dominant over other families. Finally it may be concluded that Ambadi dam is rich of fish diversity.